Myxomatous valve degeneration: A look at the latest developments of the disease - Reyes Mantilla, Juan Pablo; Gómez Torres, Fabian Alejandro; Sánchez Pico, Favio; Albarracin Navas, Javier Hernando; Toledo Caceres, Édgar Hernando (Spei Domus, 2013)
This review article is an analysis of the most recent published scientific articles about myxomatous valve degeneration (MVD) and was conducted over a five month period. The aim of this review is to consolidate information about the most recent medical developments in regards to myxomatous degeneration in the mitral valve. The authors of this article reached a consensus on both the development of the disease and the most effective type of diagnosis and treatment that is available today. Myxomatous valve degeneration is the most common heart disease in the canine population. It is identified by a loss of mechanical integrity in the heart due to structural changes in the valvular components. Degenerative changes occur due to an accumulation of mucopolysaccharides in the leaflets and chordae which affect the proper operation of the valve apparatus. This is caused by faulty coaptation of the leaflets, resulting in mitral or tricuspid regurgitation, dilated ventricles and annuli, which are lesions that eventually cause the rupture of the chordae tendineae, leading to complications or possibly death. Due to the gradual progression of the disease and the presence or absence of clinical signs, it is very important that veterinarians accurately diagnose and follow-up on these patients in order to achieve stabilization and provide a suitable prognosis and treatment plan. The current ideal treatment of the disease is a low-sodium diet, administration of the aceinhibitor (angiotensin-converting-enzyme inhibitor) spironolactone and a diuretic in order to reduce the presence of pulmonary edema and avoid the progression of the disease to congestive heart failure.
Keywords: av valves; canine; heart; Myxomatous degeneration; treatment.